Model of pedagogical support of increasing the level of self-organisation in students - Svetlana A. Kosareva (Saratov State University, 2021)
The article presents theoretical analysis of the phenomenon of self-organization and its definition and introduces the structural-functional model of pedagogical support for increasing the level of students' self-organization. It was developed due to the fact that students have well-developed skills of self-organization, since they need to cope with a large amount of autonomous work, and university graduates, since they are required to solve professional problems effectively. The purpose of the study is justification of the content of the model blocks. The hypothesis of the study is that the implementation of the model will provide an increase in the level of students' self-organization. The model includes the purpose, approaches, principles of teaching, pedagogical conditions, description of teacher and students' activities, methods, forms and means used in the educational process. The model has criteria, indicators and levels of self-organization as well. The author provides justification for the application of these approaches and principles of teaching, explains the need to create certain pedagogical conditions. Work on increasing the level of students' self-organization consists of a theoretical and practical part, which correspond to the preparatory and main stages of pedagogical support. Thus, the practical part of the work includes students' project activities aimed at compiling a textbook, which serves as a basis for training self-organization skills. The control and correction stage is connected with determining the achieved level of self-organization on the basis of its criteria and their indicators. We highlighted and gave a description of three levels of self-organization. The result of the analysis is that students' level of self-organization becomes higher.